Introduction (Itinera, 2024)
The environmental and social crisis that confront our century calls to a quest for new scenarios and landscapes and a reflection on such challenge. In this issue, the question of landscape is approached from a variety of viewpoints, ranging from the more philosophical to the strictly urbanistic. Some of the essays also focus on technology and geography. It is clear that, from engineers to biologists, from architects to the players of the art world, there is a strong interest to imagine future landscapes able to generate forms of life in which one can recognize oneself, and as such more sustainable.